Implementación de un sistema de gestión ambiental, seguridad y salud en el trabajo, conforme a las normas iso 14001:2004 y oshas 18001:2007, en la empresa mining machine & service - antamina. - Arana Castañeda, Javier Alonso (2013)
The subject of the thesis was focused on showing the implementation of an Environmental, Occupational Health and Safety Management System, which meets the international standard ISO 14001:2004 and OHSAS 18001:2007, as a practical application, this thesis describes and comments Implementation of Environmental, Occupational Health and Safety Management System in Mining Machine & Service Company SAC, in Compania Minera Antamina. This work is divided into 10 chapters. In the first instance there is mention of personal and environmental accidents occurred in the mining sector based on statistics from the Ministry of Energy and Mines, also referred to the background of the Implementation of Environmental Management Systems such as Occupational Safety and Health. Then we review the ISO 14001:2004 and OHSAS 18001:2007, which join us to Environmental, Occupational Health and Safety Management Systems indicating the general requirements which must have such systems and the interrelationship between them. Diagnosis was subsequently performed current business against the requirements of the standard, as well as a FODA analysis of the company and reviewing safety indices in 2011 and 2012. Finally the Environmental, Occupational Health and Safety Management System was implemented, which establish the procedures to adjust the company to the requirements of ISO 14001:2004 and OHSAS 18001:2007.